PENGARUH MEDIA PEMBELAJARAN INTERAKTIF KAHOOT UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 18 BANDA ACEH - Miranda, Ana; Puspita Sari, Nena; Azkia, Nura (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low science and social studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 18 Banda Aceh. The objective of this study was to determine the effect of using the Kahoot interactive learning media on the IPAS learning outcomes of fifth-grade students at SD Negeri 18 Banda Aceh. This study employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The sample consisted of 32 students selected using a saturated sampling technique. Data were collected through learning achievement tests and documentation, while data analysis was conducted using the normality test, Paired Sample t-Test, and N-Gain analysis. The results showed that the mean pretest score increased from 61.81 to 81.09 on the posttest. The Paired Sample t-Test yielded a significance value of 0.000 (< 0.05), and the N-Gain score was 0.50, which was categorized as moderate. Therefore, the Kahoot interactive learning media was found to be effective in improving the IPAS learning outcomes of fifth-grade students at SD Negeri 18 Banda Aceh.